Energy demand in Ghana: A disaggregated analysis. (January 2016) - Mensah, Justice Tei; Marbuah, George; Amoah, Anthony
Abstract: This paper presents a comprehensive analysis of energy demand in Ghana by estimating demand functions for key disaggregated energy components including gasoline, diesel, liquefied petroleum gas (LPG), kerosene, biomass, residual fuel oil (RFO) and electricity. Our results show that energy prices, income, urbanization and economic structure are significant demand drivers of the different energy types in Ghana with varying estimated elasticities. Further, there is evidence of high degree of inter-fuel substitution in energy demand in Ghana, particularly from gasoline, diesel and kerosene towards LPG consumption. We recommend, among different policy options, a customization of energy price subsidization policies, especially on LPG, to reduce the unintended beneficiary dilemma or spillover effect of current government policy. Other policies such as intensification of energy conservation programs and market entry of independent power trading companies to enhance energy service delivery through competition are also discussed.